Modality Switching in a Property Verification Task: An ERP Study of What Happens When Candles Flicker after High Heels Click - Collins, Jennifer; Pecher, Diane; Zeelenberg, René; Coulson, Seana (Frontiers in Psychology, 2011)
The perceptual modalities associated with property words, such as flicker or click, have previously been demonstrated to affect subsequent property verification judgments (Pecher et al., 2003). Known as the conceptual modality switch effect, this finding supports the claim that brain systems for perception and action help subserve the representation of concepts. The present study addressed the cognitive and neural substrate of this effect by recording event-related potentials (ERPs) as participants performed a property verification task with visual or auditory properties in key trials. We found that for visual property verifications, modality switching was associated with an increased amplitude N400. For auditory verifications, switching led to a larger late positive complex (LPC). Observed ERP effects of modality switching suggest property words access perceptual brain systems. Moreover, the timing and pattern of the effects suggest perceptual systems impact the decision-making stage in the verification of auditory properties, and the semantic stage in the verification of visual properties.